PANDANGAN MADZHAB SYAFI’I TERHADAP TANAH HIBAH YANG DIJADIKAN MASJID DI DUSUN CANGGI KABUPATEN PASURUAN - Abdul Fattah (al-Rasῑkh: Jurnal Hukum Islam, 2022)
This study aims to find out the process of the occurrence of land grants that were turned into mosques according to Imam Syafi'i's view and to know the views of the Syafi'i Madzhab on the existence of land grants that were turned into mosques. This study uses a type of qualitative research. The results of this study are that according to the opinion of Imam Syafi'i it is stated that it is forbidden (permissible) to exchange land grants that are used as mosques, this opinion is based on the hadith of Rasulullah SAW which originates from Ibn Umar which in essence donated assets may not be traded and may not be donated and also inherited . According to Islamic law circles, the donated assets are left as they are, so they cannot be exchanged and changed, even though the donated land has more benefits. In contrast to the Islamic legal opinion above, it turns out that the community of Dusun Canggi, Sekarmojo Village, Pasuruan Regency stated that it is permissible for the law to exchange land grants that are used as mosques. This has happened in Dusun Canggi, Sekarmojo Village, although not many. The reason they allow it is because there are more benefits, so they think it is permissible. The permission to exchange the donated land for the mosque is an initiative of the grant management agency, so that with their joint decision there has been an exchange of the donated land for the mosque.